2020
DOI: 10.22541/au.160217176.66860225/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for severe and critically ill COVID-19 patients: a review

Abstract: The coronavirus disease 2019 pandemic (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused an unprecedented global social and economic impact, and numerous deaths. Many risk factors have been identified in the progression of COVID-19 into a severe and critical stage, including old age, male gender, underlying comorbidities such as hypertension, diabetes, obesity, chronic lung disease, heart, liver and kidney diseases, tumors, clinically apparent immunodeficiencies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
145
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(162 citation statements)
references
References 0 publications
11
145
2
2
Order By: Relevance
“…Severe liver disease is a serious condition with a reduced life expectancy and is associated with immune deficiency. In line with our findings, severe liver disease has previously been reported to be associated with a several-fold increase in mortality in both COVID-19 (36) and influenza (37). Malignancy was not associated with ICU admission for influenza or COVID-19 in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Severe liver disease is a serious condition with a reduced life expectancy and is associated with immune deficiency. In line with our findings, severe liver disease has previously been reported to be associated with a several-fold increase in mortality in both COVID-19 (36) and influenza (37). Malignancy was not associated with ICU admission for influenza or COVID-19 in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Increasing amounts of data are showing hat COVID-19 severity is related to sex. [23][24][25] A retrospective cohort study in China showed that male sex is a major risk factor for higher disease severity and mortality. 26 A web-based COVID-19 survey in Italy that included 6873 participants (mean age, 47.9 AE 14.1 years; 65.8% women) showed that women had lower odds than men of a positive nasopharyngeal swab test (adjusted OR, 0.75; 95% CI, 0.66-0.85) and of having a severe infection (adjusted OR, 0.46; 95% CI, 0.37-0.57).…”
Section: Discussionmentioning
confidence: 99%
“…All patients were evaluated medically, including severe COVID‐19 risk factors (at least one of the following: age>59, hypertension, coronary heart disease, diabetes, obesity, active neoplastic disease) 22 . Additionally, in a randomly chosen subgroup of 79 participants, the basal serum tryptase concentration was analysed.…”
Section: Methodsmentioning
confidence: 99%